The Impact of Financial Performance on Initial Returns of Companies Conducting Initial Public Offerings in Indonesia - Fariskya, Sabela Nur; Sari, Shinta Permata (E-Jurnal Akuntansi, 2024)
The initial public offering (IPO) serves as a strategy for acquiring financial resources aimed at enhancing company performance. This study seeks to analyze the impact of return on assets (ROA), earnings per share (EPS), debt-equity ratio (DER), and current ratio on the initial return of IPOs. The research population comprises companies that conducted their first stock offering and were listed on the Indonesian Stock Exchange between 2020 and 2022. The sampling technique employed was purposive sampling, resulting in a total sample of 80 companies. The analytical technique utilized was multiple regression, conducted using SPSS version 25. The findings indicate that ROA and the debt-equity ratio exert no significant influence on the initial return, whereas EPS and the current ratio positively influence the initial return. Keywords: Return on Asset; Earning per Share; Debt Equity Ratio; Current Ratio; Initial Return.